Analysis of the Roles and Functions of Islamic Education Leaders in Improving Educational Services - Ahmad Suprayitno (Journal of Innovative Islamic Education Management, 2025)
The main issue underlying this study is the suboptimal role of Islamic educational leaders in carrying out their duties and functions comprehensively, resulting in the quality of educational services in many institutions not meeting the expected standards. Weak leadership in the areas of planning, organizing, actuating, and controlling has led to ineffective and unsustainable learning services, administrative services, and character development programs. This study aims to analyze the duties and functions of Islamic educational leaders and their contribution to improving the quality of educational services. The research employs a library research method with a descriptive qualitative approach, analyzing various academic sources such as books, scholarly journals, and relevant research documents. The findings reveal that leaders who understand Islamic values and modern leadership theories are able to carry out managerial and spiritual functions synergistically to enhance educational service quality. Visionary, adaptive, communicative, and integrity-driven leaders are proven to encourage the creation of higher-quality, responsive, and character-oriented educational services. The implications of this study emphasize that improving the quality of Islamic education depends heavily on leadership capacity, thus requiring continuous leadership development, professional management practices, and the integration of Islamic values throughout all educational service processes.